Theoretical Framework for the Functional Mechanism of Sustainable Urban Governance - Toloue-Hayat-Azar, Parisa (European Journal of Sustainable Development, 2017)
An important factor in defining a framework is assessing exactly which elements are involved and how they can interact with each other. Throughout the academic literature, a lot of governance modes have been suggested, based on case study articles that have taken into consideration the governance of different cities based on their characteristics. However, there is a lack on convergence on the frameworks that each of these studies have used, which makes the comparison between the different studies arduous. Furthermore, these modal classifications cannot really demonstrate their ability in solving economic, social and environmental concerns that cities are trying to solve. This article aims to analyse the governing elements of each mode through the introduction of a unique framework for future urban governance studies and by studying the development of different modes of governance throughout the historical period involved. Keywords: Governance, Activity Theory, Sustainable Development